Do Workers In Chile Choose Informal Employment? : A Dynamic Analysis of Sector Choice - Packard, Truman (The World Bank, 2007)
The degree to which a labor market is segmented and jobs in the formal sector of the economy are rationed is critical to the analysis of coverage of social insurance and pensions. Using unique panel data spanning the 1998-99 contraction in Chile, the author finds little evidence that self-employment is the residual sector of a dualistic labor market, as is often depicted in the literature. Data on transitions between sectors show that self-employment is not a free-entry sector, and that entrepreneurs can be "pushed" out of self-employment just as others are pushed out of formal employment during economic downturns. But employment without a contract does exhibit many of the features of the free-entry, employment safety net depicted in the dualistic literature. An annex to this paper presents supportive evidence from static analysis of selection-corrected wage differentials and a comment on the drawbacks of this approach